FAKTOR RISIKO KEJADIAN DIARE PADA BALITA DI PUSKESMAS P BANJARMASIN - Muhammad Mukhlis Solehin; Nirma Yunita (Politeknik Unggulan Kalimantan, 2025)
Diarrhea remains a leading cause of morbidity and mortality among toddlers, especially in developing countries like Indonesia. This study aimed to describe the incidence of diarrhea and its associated risk factors among toddlers in the working area of P Public Health Center, Banjarmasin. A descriptive study with a cross-sectional approach was used. A total of 265 toddlers were selected using total sampling. Data were collected through questionnaires and observation and analyzed descriptively. Results showed that the prevalence of diarrhea was 2.39%. Most toddlers were aged 1–12 months (30.57%). The most dominant risk factor was poor handwashing behavior (52%), followed by inadequate sanitation and unsafe water access (48%). Exclusive breastfeeding was not found to be a risk factor among diarrhea cases. These findings indicate that hygiene behavior and environmental sanitation play crucial roles in preventing diarrhea. Health workers should provide educational and promotive interventions to raise public awareness about personal and environmental hygiene.